Characteristics of the short-term temporal variations of multi-constellation and multi-frequency GNSS receiver differential phase biases - MI Xiaolong (Surveying and Mapping Press, 2021)
With the completion of the BeiDou-3 Navigation Satellite System (BDS-3) and the development of Galileo and quasi-zenith satellite system (QZSS), more and more satellites can be used to retrieve the atmospheric ionosphere. Generally, the short-time variation of receiver differential code biases (DCB) is considered as an important error source for ionospheric inversion using Global Navigation Satellite System (GNSS). However, some studies have shown that the short-time variation of receiver differential phase biases (DPB) may also affect the accuracy and reliability of ionospheric inversion. This paper presents a method to estimate the receiver DPB based on the single-differenced (SD) model without changing the reference satellite, which can realize the continuous estimation of the receiver DPB. DPB of the overlapping frequency combination of BDS-3, Galileo, GPS and QZSS is analyzed based on data collected from several multi-frequency and multi-constellation receivers capable of tracking the new signals of the BDS-3. The results show that ① The intraday changes of DPB of BDS-3, Galileo, GPS and QZSS are obvious and have a strong correlation with temperature. ② There is a strong correlation between the DPB of the overlapping frequency combinations of BDS-3, Galileo, GPS and QZSS. ③ There is a significant correlation between changes in DPB based on the baseline of the same type of combination.